DNS of a single low-speed streak subject to spanwise wall oscillations - Negi, Prabal Singh (2016)
Direct numerical simulation (DNS) is performed to study the effect of steady streamwise oscillations of the spanwise wall velocity on a single low-speed streak in a laminar boundary layer. The low-speed streak is numerically generated by simulating a screen which creates a momentum loss. The wall oscillations are shown to reduce the skin friction which drops below the laminar Blasius flow value (without the presence of streaks) for certain cases of wall oscillations. In addition, the peak streamwise velocity fluctuation of the streaks are reduced drastically by up to 90 %, the trend in reduction being monotonic with respect to higher amplitude oscillations. The effect of oscillation is also studied during transition (breakdown of the streak) and it is found that the optimum wavenumber of the oscillation changes by nearly an order of magnitude during transition. The reduction of peak streamwise velocity fluctuations shows a phase dependent behaviour which is explained based on the regeneration of turbulence in the absence of a streamwise gradient of the spanwise velocity. The general trend of reduction in streamwise fluctuations across different wavenumbers does not correlate well with the decrease in skin friction. A much better qualitative correlation is found when comparing the relative trends for skin friction and wall-normal velocity fluctuations for different oscillation wavenumbers.